1992
DOI: 10.1007/bf00223982
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic recombination in maize populations using molecular markers

Abstract: Variation in recombination rate is important to plant breeders since a major objective is to obtain favorable recombinants of linked genes. The ability to increase recombination (R) in circumstances in which favorable and unvavorable genes are linked (Corn Belt x exotic populations) and to decrease recombination when many favorable genes are linked (narrow-based, elite populations) would be of immense value. However, the concept of variation in recombination frequencies between linked genes has received limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…The map length of an interspecific hybrid has been recognized as being shorter than that of an intraspecific hybrid Stec, 1991, 1993). Variability in recombination rates in maize was first reported in 1918 by Bregger and later confirmed using molecular markers (Tulsieram et al, 1992). Segregation distortion was first reported in maize by Mangelsdorf and Jones (1926) based on a linkage between the gametophyte factor Ga1 and the Su allele for starchy endosperm.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The map length of an interspecific hybrid has been recognized as being shorter than that of an intraspecific hybrid Stec, 1991, 1993). Variability in recombination rates in maize was first reported in 1918 by Bregger and later confirmed using molecular markers (Tulsieram et al, 1992). Segregation distortion was first reported in maize by Mangelsdorf and Jones (1926) based on a linkage between the gametophyte factor Ga1 and the Su allele for starchy endosperm.…”
Section: Introductionmentioning
confidence: 90%
“…A study by Tulsieram et al (1992) suggested that cis-factors potentially influence recombination rates. The first explanation for recombination shrinkage was based on the assumption that base-sequence homology determines where crossing-over will occur (Borts and Haber, 1987).…”
Section: Recombination Frequency Variability and Recombination Shrinkagementioning
confidence: 99%
“…Recombination fraction can also vary depending on the environment (Ihrke & Kronstad, 1975;Zhuchenko & Korol, 1983). The influence of temperature has been particularly studied and reported (Allard, 1963;Towe & Stadler, 1964;Lu, 1974;Rose & Baillie, 1979;Tulsieram et a!., 1992). These examples of recombination differences raise several problems concerning the extent of heterogeneity and its potential impact on map merging, breeding applications, and positional cloning.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, recombination rates vary among accessions (Sanchez-Moran et al 2002). In maize, heterogeneity in recombination frequencies has been well documented within corn belt (Beavis and Grant 1991;Tulsieram et al 1992), corn belt 3 exotic germplasm (Tulsieram et al 1992), synthetic (Fatmi et al 1993), exotic, and teosinte-maize hybrid (Williams et al 1995) mapping populations and has often confounded the generation of composite genetic maps. Recombination rates in intervals with heterogenous frequencies varied two-to threefold among diverse mapping populations (Williams et al 1995).…”
mentioning
confidence: 99%